2021
DOI: 10.1155/2021/5570806
|View full text |Cite
|
Sign up to set email alerts
|

The Use of Sugarcane Bagasse to Remove the Organic Dyes from Wastewater

Abstract: In the present study, the potential of sugarcane bagasse (SCB) was evaluated by methylene blue (MB) retention. The selected low-cost adsorbent was characterized by scanning electron microscopy (SEM) coupled with energy-dispersive X-ray spectroscopy (EDX), Fourier transform infrared spectroscopy (FTIR), BET method, and determination of the point of zero charge (pHzpc). Batch kinetic and isothermal studies were performed to examine the effects of contact time, initial dye concentration, adsorbent dose, pH, and t… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
13
1
3

Year Published

2022
2022
2024
2024

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 27 publications
(20 citation statements)
references
References 36 publications
(52 reference statements)
1
13
1
3
Order By: Relevance
“…Specifically, cellulase hydrolysis led to larger TV (from 0.004 to 0.01 cm 3 /g) and APS (from 47.5 to 122.1 nm) in SCBE, presumably resulting from the breakdown of cellulose chain by cellulase. In previous reports, without water extraction for soluble sugars, SCB was characterized non-porous or macro-porous based on the SSA of 0.73 m 2 /g, TV of 0.0007 cm 3 /g, and APS of 5.73 nm, respectively (Kerrou et al, 2021), which were apparently lower than the values in this study by 5 to 8 folds. It is apparent that prior water extraction of soluble sugars spares more pore space in SCB that is originally taken by sugar molecules.…”
Section: Effect Of Persulfate Pretreatment or Laccase Addition On Enz...contrasting
confidence: 80%
See 4 more Smart Citations
“…Specifically, cellulase hydrolysis led to larger TV (from 0.004 to 0.01 cm 3 /g) and APS (from 47.5 to 122.1 nm) in SCBE, presumably resulting from the breakdown of cellulose chain by cellulase. In previous reports, without water extraction for soluble sugars, SCB was characterized non-porous or macro-porous based on the SSA of 0.73 m 2 /g, TV of 0.0007 cm 3 /g, and APS of 5.73 nm, respectively (Kerrou et al, 2021), which were apparently lower than the values in this study by 5 to 8 folds. It is apparent that prior water extraction of soluble sugars spares more pore space in SCB that is originally taken by sugar molecules.…”
Section: Effect Of Persulfate Pretreatment or Laccase Addition On Enz...contrasting
confidence: 80%
“…For both MB and Cu 2+ , the adsorption by the four adsorbents was fast and equilibrium was reached within 60 min. Similarly, another study showed that adsorption of MB on SCB was reached in only 20 min ( Kerrou et al, 2021 ). In comparison of the two adsorbents, the time for adsorption equilibrium by SCBE was slightly shorter than that by SCB, even though SCBE showed reduced adsorption capacity, as revealed in the later section.…”
Section: Resultsmentioning
confidence: 92%
See 3 more Smart Citations